Insights into phytoremediation solutions for environmental recovery - Samardjieva, Kalina A. (2012)
Our environment is contaminated with organic and inorganic compounds released by anthropogenic activities that cause negative impacts on biological productivity and ecosystem sustainability and place human health at risk. Within the available remediation technologies, phytoremediation has emerged with high potential due to its reduced environmental impacts and economic costs. The research into phytoremediation has developed through a wide array of approaches, which also pertains to its inherent interdisciplinary characteristics, towards enhancing the potential of the technology for application in the field. Numerous patents present molecular solutions through which plants can be engineered to display improvements in key characteristics, such as the tolerance, uptake and accumulation of contaminants. The manipulation of plant growth and of the physico-chemical characteristics of the contaminated environments in order to enhance the remediation potential has also been the focus of several issued patents. This review attempts to highlight the most relevant patented advances in phytoremediation and to emphasise recent research efforts through which this green technology might be expected to develop into a commercially competitive alternative to other remediation methods.